Monitoramento do mandarová da mandioca (Erinnyis ello L. 1758) para o controle com baculovirus (Baculovirus erinnyis) - Aguiar, Eduardo Barreto [UNESP]; Lorenzi, José Osmar; Monteiro, Domingos Antônio; Bicudo, Silvio José [UNESP] (My University, 2010)
Hornworm, Erinnyis ello L. (Lepidoptera: Sphingidae), an defoliator insect that consumes cassava leaves in larval phase. In Brazil, is the most important pest of the culture. The control with Baculovirus erinnyis has been shown efficient and viable alternative, as environmental as economical point of view. The present work was accomplished in Bahia State, Brazil, from 2004 to 2006 in a 3.000 ha continuous area of cassava farming. The objective of this work is to verify the efficiency of the proposed monitoring for the control of the hornworm with B. erinnyis. The monitoring was accomplished counting the E. ello adults captured daily by luminous trap, and eggs and larvae presents in plants, after identification of adults flights (above 50 adults captured.day-1). It was considered as damage level (ND) the minimum number of two larvae per plant in second and third instar, when the control with B. erinnyis were done. The adults counting by luminous trap method was efficient in the identification of E. ello adult flights, and it allowed to optimize efficiently the eggs and larvae counting in the field when the infestations happened. With the proposed monitoring, it is possible the control of E. ello infestations with use of B. erinnyi.

O Mandarová da mandioca, Erinnyis ello L. (Lepidoptera: Sphingidae), é um inseto que consome as folhas da mandioca em sua fase larval. No Brasil é considerada uma das pragas mais importantes dessa cultura. Dentre os diversos métodos de controle utilizados o controle com Baculovirus erinnyis tem se mostrado eficiente, e uma boa alternativa em termos ambientais e econômicos. O objetivo deste trabalho foi verificar a eficiência do monitoramento proposto, para o controle do mandarová com o B. erinnyis. O monitoramento foi realizado com a contagem de adultos de E. ello capturados diariamente em armadilha luminosa, e contagem de ovos e larvas nas plantas, após a identificação de revoadas de adultos (acima de 50 adultos capturados.dia-1). Após a identificação do nível de dano (ND) o controle foi realizado com B. erinnyis. A contagem de adultos com armadilha luminosa mostrou-se eficiente na identificação de revoadas de E. ello, e permitiu de maneira otimizada o monitoramento da infestação de ovos e larvas no campo, no período que ocorreram. A partir da utilização dessa metodologia, é possível o controle das infestações de E. ello em grandes áreas, com a utilização do B. erinnyis.
Monitoring of hornworm (Erinnyis ello) for the control with baculovirus (Baculovirus erinnyis)
Keywords: Manihot esculenta Crantz; Biological control; Luminous trap; Manihot esculenta; Controle biológico; Armadilha luminosa